Unexpected Management Behaviors in Adolescents With Type 1 Diabetes Using Sensor-Augmented Pump Therapy. (May 2018) - Abraham, Mary Binsu; Heels, Kristine; Nicholas, Jennifer A.; Cole, Carol; Gebert, Rebecca; Klimek, Julie; Jopling, Tracey; Ambler, Geoffrey; Cameron, Fergus; Davis, Elizabeth; Jones, Timothy W.
Background: Continuous glucose monitoring can improve glycemic outcomes in individuals with type 1 diabetes. However, the constant exposure to real-time glucose levels can sometimes lead the individual to make some risky choices to address the glycemic excursions. Hence, the purpose of this study was to explore the aberrant management behaviors of youth with type 1 diabetes on sensor-augmented pump therapy (SAPT). Methods: Participants in a clinical trial using SAPT on Medtronic MiniMed™ 640G pump who experienced deteriorating glycemic control or unexplained hypoglycemia were identified by the health care professional. The pump and/or sensor data uploaded to CareLink™ Therapy Management Software were reviewed in these participants. Results: Uncharacteristic management behaviors were identified in five adolescent males. Continuous exposure to high glucose levels resulted in obsessive behaviors displaying a perfectionistic attitude in two participants. Multiple boluses were delivered frequently as uneaten carbohydrates in participant 1 while participant 2 resorted to delivery of extra insulin by cannula fills. In contrast, participant 3 chose to remain hyperglycemic to avoid weight gain while participant 4 trusted the system and used sensor glucose readings for calibrations, with resultant deterioration in glycemic control in both participants. On the other hand, participant 5, due to mistrust in the pump suspend function, consumed carbohydrates with downward glucose trends with rebound hyperglycemia. Conclusions: Constant exposure to real-time data can lead to unsafe management responses in adolescents with the behavior influenced by trust or mistrust in the system. Adolescents should be empowered with problem-solving strategies for safe management.